IEEE 802.15.4 a developing standard for low-power low-cost wireless personal area networks. - Gutierrez, J.A (IEEE Network : the magazine of global information exchange)
A low-rate wireless personal area network, or LR-WPAN, is a network designed for low-cost very-low-power short-range wireless communications. Until now, the main focus in the wireless industry has been on communications. Until now, the main focus in the wireless industry has been on communication with higher data throughput, leaving out a set of applications requiring simple wireless connectivity with relaxed throughput and latency requirements. LR-WPANs will connect devices that previously have not been networked and allow applications that cannot use current wireless specifications, including applications in fields such as industrial, agricultural, vehicular, residential, medical sensors and actuators. TaskGroup 4 of the IEEE 802.14 Wireless personal Area Network working group is currently working to define a wireless communication standard for LR-WPANs. This article discusses the technical considerations and system requirements necessary when implementing a low-cost low-power wireless personal area network and provides an overview of the unique applications such a technology will enable